Analisis Clustering Pengguna SIKP FTI UKSW Menggunakan User Experience Questionnaire - Putra, Marcellino Adi; Fibriani, Charitas (STMIK Banjarbaru, 2025)
The ease of access to technology today encourages the use of technology to improve productivity and efficiency in the lecture process, including in the lecture process at FTI UKSW (Faculty of Information Technology, Satya Wacana Christian University) which uses SIKP (Practical Work Information System). This study identifies the grouping/clustering of SIKP user students based on student user experience. The UEQ and Fuzzy C-Means methods are used to formulate the clustering of SIKP user students with the aim of determining the level of satisfaction of FTI UKSW students with the SIKP currently in use and hopefully providing an analysis of which parts of the FTI UKSW SIKP need to be improved. The UEQ method uses six elements, namely Attractiveness, Clarity, Efficiency, Accuracy, Stimulation, and Novelty. Meanwhile, the Fuzzy C-Means method measures the degree of membership of a data set to determine the satisfaction level grouping. Testing the accuracy of the algorithm's performance showed that the clustering process can form groupings with a level of clarity and cluster separation that provides good performance and can still be developed to obtain more optimal performance. Keywords: Clustering; User Experience Questionnaire; Fuzzy C-Means AbstrakMudahnya akses teknologi saat ini mendorong pemanfaatan teknologi untuk meningkatkan produktivitas dan efisiensi pada proses perkuliahan, termasuk pada proses perkuliahan di FTI UKSW (Fakultas Teknologi Informasi Universitas Kristen Satya Wacana) yang menggunakan SIKP (Sistem Informasi Kerja Praktek). Penelitian ini mengidentifikasi pengelompokan mahasiswa pengguna SIKP berdasarkan user experience mahasiswa. Metode UEQ dan Fuzzy C-Means adalah metode yang digunakan untuk merumuskan clustering mahasiswa pengguna SIKP dengan tujuan mengetahui tingkat kepuasan mahasiswa FTI UKSW terhadap SIKP yang digunakan saat ini dan diharapkan dapat memberikan analisis bagian mana yang perlu ditingkatkan pada SIKP FTI UKSW. Metode UEQ akan menggunakan 6 elemen yaitu Daya tarik, Kejelasan, Efisiensi, Ketepatan, Stimulasi, dan Kebaruan. Sementara itu, metode Fuzzy C-Means akan mengukur derajat keanggotaan suatu data untuk mengetahui pengelompokan tingkat kepuasan. Pengujian akurasi performa algoritma memberikan hasil bahwa proses clustering dapat membentuk pengelompokan dengan tingkat kejelasan dan pemisahan cluster yang memberikan performa baik serta masih dapat dikembangkan untuk memperoleh performa yang lebih optimal.